2015
DOI: 10.4084/mjhid.2015.004
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Alpha Thalassemia in Microcytic Anemia: A Tertiary Care Experience From North India

Abstract: IntroductionCases with microcytosis not responding adequately to iron supplementation are diagnostic dilemma and have been reported to harbor alpha (α) thalassemia mutations. The aim of this study was to determine the common α globin gene deletions in cases with microcytic anemia.MethodsFifty four patients selected (22 females and 32 males) had microcytic anemia (MCV < 80 fl, Hb <12gm/dl) with raised TRBC (> 5M/mm3) but normal Hb HPLC. They had either low or normal Transferrin Saturation (TS). Gap-PCR for four… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
7
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 32 publications
5
7
0
Order By: Relevance
“…The severe microcytosis and hypochromasia that is reported here might also be due to a coinheritance of the α 3.7 allele with other deletion type or point mutation, such as AC deletion in vicinity of the initiation codon of the − α 3.7 allele [29]. RDW_CV of the − α 3.7 heterozygous group revealed anisopoikilocytosis, in adult males and females, while in children showed mild anisopoikilocytosis, this finding is consistent with previous studies [27,30,31].…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…The severe microcytosis and hypochromasia that is reported here might also be due to a coinheritance of the α 3.7 allele with other deletion type or point mutation, such as AC deletion in vicinity of the initiation codon of the − α 3.7 allele [29]. RDW_CV of the − α 3.7 heterozygous group revealed anisopoikilocytosis, in adult males and females, while in children showed mild anisopoikilocytosis, this finding is consistent with previous studies [27,30,31].…”
Section: Discussionsupporting
confidence: 93%
“…This was previously reported [14], where alpha thalassemia trait patients were characterized by slight reduction in haemoglobin level. The MCV and MCH showed microcytosis and hypochromasia in adults, and this finding is consistent with many previous studies concerning the contribution of alpha thalassemia to microcytosis and hypochromia [20][21][22][23][24][25][26][27], while others [14,28] reported slight microcytosis and hypochromasia or sometimes normal with alpha thalassemia trait. Unlike many other similar studies that have examined the red cell indices in alpha thalassaemia, present cohort showed significantly lower MCV (52-53 fL) giving an impression of additional pathology.…”
Section: Discussionsupporting
confidence: 92%
“…This was previously reported (15) , where alpha thalassemia trait patients were characterized by slight reduction in haemoglobin level. The MCV and MCH showed microcytosis and hypochromasia in adults, and this finding is consistent with many previous studies concerning the contribution of alpha thalassemia to microcytosis and hypochromia (21,23,24,25,26,27,28,29) , while others (15,22) reported slight microcytosis and hypochromasia or sometimes normal with alpha thalassemia trait. The microcytosis and hypochromasia that reported in the current study might be due to a coinheritance of the α 3.7 allele with other deletion type or point mutation, such as AC deletion in vicinity of the initiation codon of the -α 3.7 allele.…”
Section: Discussionsupporting
confidence: 92%
“…ese results have high impact in the clinic medicine, since these hematological data are often interpreted as indicators of iron deficiency [25,26].…”
Section: Resultsmentioning
confidence: 99%